2018
DOI: 10.1371/journal.pone.0206829
|View full text |Cite
|
Sign up to set email alerts
|

Summering on the bank: Seasonal distribution and abundance of monkfish on Georges Bank

Abstract: The American monkfish is an important commercial species that is widely distributed across a range of depths and temperatures from North Carolina to southern Nova Scotia, including on Georges Bank. We examined changes in the seasonal distribution and relative abundance of monkfish in the scallop access areas in Closed Area I and Closed Area II on Georges Bank using catch data from a three-year seasonal scallop dredge survey. Over the course of the survey, more than 6,000 monkfish were caught and measured, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This suggested that anglerfish dispersed from inshore grounds in autumn, and Shetland fishermen informed that the areas toward the shelf edge were targeted in the winter period due to high catch rates (Laurenson et al, 2005). Such migration was also shown for L. americanus on Georges Bank (Siemann et al, 2018). Similar seasonal shifts in distribution have been observed for other fish species on the Faroe Plateau, including cod (Tåning, 1940;Ottosen et al, 2017), saithe (Pollachius virens) (Homrum, 2012) and plaice (Pleuronectes platessa) (Tåning, 1943).…”
Section: Seasonal Migration and Depth Distributionmentioning
confidence: 83%
“…This suggested that anglerfish dispersed from inshore grounds in autumn, and Shetland fishermen informed that the areas toward the shelf edge were targeted in the winter period due to high catch rates (Laurenson et al, 2005). Such migration was also shown for L. americanus on Georges Bank (Siemann et al, 2018). Similar seasonal shifts in distribution have been observed for other fish species on the Faroe Plateau, including cod (Tåning, 1940;Ottosen et al, 2017), saithe (Pollachius virens) (Homrum, 2012) and plaice (Pleuronectes platessa) (Tåning, 1943).…”
Section: Seasonal Migration and Depth Distributionmentioning
confidence: 83%
“…The catecholamines (adrenaline and noradrenaline) released with stress are known to increase f H and affect energy mobilization by gluconeogenesis and glycogenolysis in fish (Madaro et al, 2015). Thus, several studies have shown that elevated f H can be used as an indicator of stress in several fish species, including farmed Atlantic salmon (Brijs et al, 2018, 2019; Føre et al, 2021; Hvas et al, 2020a; Mignucci et al, 2021; Siemann et al, 2018; Warren‐Myers et al, 2021; Yousaf et al, 2022; Zrini et al, 2021; Zrini & Gamperl, 2021). To determine the continuous f H in free‐swimming fish, the abovementioned studies used fully implantable tags.…”
Section: Introductionmentioning
confidence: 99%
“…One such example is Star Oddi's DST milli‐HRT loggers which measure f H and temperature. Recently, these loggers have been widely used in different experimental settings in several fish species including salmonids (Brijs et al, 2018; Einarsson et al, 2018; Ekstrom et al, 2018; Halsey et al, 2018; Norling, 2017; Siemann et al, 2018; Yousaf et al, 2022).…”
Section: Introductionmentioning
confidence: 99%